Co-occurrence of Sympatric Poroderma Species - Watson, Ralph Gareth Andrew (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Species exploiting similar ecological niches are expected to adapt their behaviour, which can either promote or hinder coexistence. This study examined the ecological (dis)similarity between the endemic Poroderma africanum (pyjama catshark) and Poroderma pantherinum (leopard catshark) in Mossel Bay, South Africa. The co-occurrence of these species was examined along the ecological axes of time, trophic position and space, between October 2015 and April 2018, through the use of Baited Remote Underwater Videos (BRUV), gastric lavage, and acoustic telemetry. Through the deployment of 197 BRUVs, P. africanum showed a seasonal, higher Relative Abundance (RA = 0.52), occurring more frequently during winter months, while showing an overall decline in RA over the course of the study period. Poroderma pantherinum on the other hand, showed a lower, unseasonal RA (0.20), remaining relatively stable throughout the study period. The BRUV deployments indicated that the two species showed a positive co-occurrence with one other, being sighted in BRUV deployments more frequently together as opposed to in isolation/at random. Acoustic telemetry indicated that the two species were active during different diel periods, influenced by a complex combination of tidal and diel rhythms, while P. pantherinum showed a higher residency compared to P. africanum (P. pantherinum: Continuous Residency Time (CRT)24 = 3.32 days (mean), 95% CI: 2.53"“4.11 days; P. africanum: CRT24 = 2.01 days, 95% CI: 1.66"“2.36 days). While the two species are sympatric in nature, and have an overlapping, endemic, distribution, acoustic telemetry indicated that 1 ABSTRACT P. africanum showed higher degrees of movement throughout the acoustic receiver array (P. africanum: edge density (ED) = 0.25; P. pantherinum: ED = 0.12); however, certain areas of the bay showed to be of high importance for both species. Both species revealed high levels of intra- and inter-specific variation in both residency and movement behaviour. Gastric lavage indicated partially overlapping trophic niches, between the two Poroderma spp. Poroderma africanum had a generalist diet, dominated by teleosts (Index of Relative Importance (IRI)% = 22.69), octopus (IRI% = 11.48) and discarded bait (IRI% = 64.54), while P. pantherinum showed indications of being a specialist predator, with a diet dominated by cephalopods (IRI% = 83.68). The two Poroderma spp. showed a partially overlapping, but separate trophic niches, while displaying spatial dissimilarity in diet. The study suggests that the two species are able to coexist within the same geographical area through niche differentiation across trophic and temporal ecological axes, with varying spatial use. The intra- and inter-specific differences between the two species may complicate elasmobranch management efforts for these co-occurring endemic catsharks, and as such, efforts should follow either an individual species approach, which is often not feasible, or an ecosystem-based approach, as opposed to considering the genus as a whole.
Keywords: Scyliorhinidae -- South Africa Mossel Bay; Coexistence of species; Leopard catshark; Poroderma africanum; Underwater acoustic telemetry; Gastric lavage; Baited remote underwater video